The Unrecognized Effects of Phosphodiesterase 4 on Epithelial Cells in Pulmonary Inflammation - Konrad, Franziska M.; Bury, Annette; Schick, Martin A.; Ngamsri, Kristian-Christos; Reutershan, Jörg (PLOS ONE, 2015)
Acute pulmonary inflammation is characterized by migration of polymorphonuclear neutrophils (PMNs) into the different compartments of the lung, passing an endothelial and epithelial barrier. Recent studies showed evidence that phosphodiesterase (PDE)4-inhibitors stabilized endothelial cells. PDE4B and PDE4D subtypes play a pivotal role in inflammation, whereas blocking PDE4D is suspected to cause gastrointestinal side effects. We thought to investigate the particular role of the PDE4-inhibitors roflumilast and rolipram on lung epithelium. Acute pulmonary inflammation was induced by inhalation of LPS. PDE4-inhibitors were administered i.p. or nebulized after inflammation. The impact of PDE4-inhibitors on PMN migration was evaluated in vivo and in vitro. Microvascular permeability, cytokine levels, and PDE4B and PDE4D expression were analyzed. In vivo, both PDE4-inhibitors decreased transendothelial and transepithelial migration even when administered after inflammation, whereas roflumilast showed a superior effect compared to rolipram on the epithelium. Both inhibitors decreased TNFα, IL6, and CXCL2/3. CXCL1, the strong PMN chemoattractant secreted by the epithelium, was significantly more reduced by roflumilast. In vitro assays with human epithelium also emphasized the pivotal role of roflumilast on the epithelium. Additionally, LPS-induced stress fibers, an essential requirement for a direct migration of PMNs into the alveolar space, were predominantly reduced by roflumilast. Expression of PDE4B and PDE4D were both increased in the lungs by LPS, PDE4-inhibitors decreased mainly PDE4B. The topical administration of PDE4-inhibitors was also effective in curbing down PMN migration, further highlighting the clinical potential of these compounds. In pulmonary epithelial cells, both subtypes were found coexistent around the nucleus and the cytoplasm. In these epithelial cells, LPS increased PDE4B and, to a lesser extend, PDE4D, whereas the effect of the inhibitors was prominent on the PDE4B subtype. In conclusion, we determined the pivotal role of the PDE4-inhibitor roflumilast on lung epithelium and emphasized its main effect on PDE4B in hyperinflammation.